USP14 is a deubiquitinase for Ku70 and critical determinant of non-homologous end joining repair in autophagy and PTEN-deficient cells. Issue 2 (19th November 2019) - Sharma, Arishya; Alswillah, Turkeya; Kapoor, Isha; Debjani, Pal; Willard, Belinda; Summers, Matthew K; Gong, Zihua; Almasan, Alexandru
Abstract: Ionizing radiation (IR)-induced DNA double-strand breaks (DSBs) are predominantly repaired by non-homologous end joining (NHEJ). IR-induced DNA damage activates autophagy, an intracellular degradation process that delivers cytoplasmic components to the lysosome. We identified the deubiquitinase USP14 as a novel autophagy substrate and a regulator of IR-induced DNA damage response (DDR) signaling. Inhibition of autophagy increased levels and DSB recruitment of USP14. USP14 antagonized RNF168-dependent ubiquitin signaling and downstream 53BP1 chromatin recruitment. Here we show that autophagy-deficient cells are defective in NHEJ, as indicated by decreased IR-induced foci (IRIF) formation by pS2056-, pT2609-DNA-PKcs, pS1778-53BP1, RIF1 and a reporter assay activation. Moreover, chromatin recruitment of key NHEJ proteins, including, Ku70, Ku80, DNA-PKcs and XLF was diminished in autophagy-deficient cells. USP14 inhibition rescued the activity of NHEJ-DDR proteins in autophagy-deficient cells. Mass spectrometric analysis identified USP14 interaction with core NHEJ proteins, including Ku70, which was validated by co-immunoprecipitation. An in vitro assay revealed that USP14 targeted Ku70 for deubiquitination. AKT, which mediates Ser432-USP14 phosphorylation, was required for IRIF formation by USP14. Similar to USP14 block, AKT inhibition rescued the activity of NHEJ-DDR proteins in autophagy- and PTEN-deficient cells. These findings reveal a novel negative PTEN/Akt-dependent regulation of NHEJ by USP14.